ON THE ROLE OF A FOREIGN LANGUAGE IN THE PROFESSIONAL TRAINING OF FUTURE SPECIALISTS - Kamalova Kadriya Fyodorovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article is devoted to the problem of teaching foreign languages to university students. Particular attention is paid to the role of a foreign language in vocationally-oriented training of students of technical universities. Outlined the goals and objectives of the discipline based on the development of professional and socio-cultural communication. Shows the importance of learning a foreign language as an integral component of the professional training of future specialists.